Mengelola Keuangan Keluarga yang Baik di Desa Gumuk Rejo - Rusmiati Rusmiati; Sigit Priyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2019)
The main problem of a family that is always there is usually about finance. Could be due to lack of money, excess money, or because of confusion about how to manage money for people whose income is mediocre, while the needs always exceed income. But the mouth of it all, the key word is how to manage family or personal finances with smart, careful and the best. Managing finance is the main key in achieving financial success. Especially with the increasing cost of living in today's era requires us to be smarter in managing finances so as not to get into debt. Therefore, we must manage family finances so that expenses are not greater than income.